Microwave reflectometer-sensor system for soil quality processing in Malaysia [electronic resource] - Then Yi Lung, 1988-; Fakulti Kejuruteraan Elektrik (2012)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2012